COMPARISON OF CONCEPTUAL PRINCIPLES OF PRESCHOOL EDUCATION IN UKRAINE AND GERMANY IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES - Honcharuk, Maryna (Continuing Professional Education: Theory and Practice, 2025)
The article focuses on comparing the conceptual foundations of early childhood education in Ukraine and the Federal Republic of Germany within the context of European integration. The author conducts a comparison based on four key criteria: regulatory-legal, organizational-institutional, content-procedural, and inclusive-developmental. The article examines the specificities of regulatory-legal frameworks for early childhood education in both countries, the organization of early childhood education institution networks and forms of learning, content and procedural aspects of the educational process, as well as issues of ensuring inclusion and development of early childhood education systems. Similar developmental trends have been identified, particularly orientation towards child-centeredness, inclusivity, variability of educational programmes, and integration of digital technologies. Distinctive features have been established, which are determined by national characteristics, historical development, and administrative-territorial structure of the countries. The German system is characterized by decentralized management, diversity of early childhood institution forms (forest, religious, home-type), and practical orientation of the educational process. The Ukrainian system demonstrates remarkable progress in modernization aligned with European standards, including a successful shift from custodial care models to contemporary educational frameworks, dynamic expansion of institutional networks, and effective implementation of inclusive practices despite wartime challenges. Prospective directions for implementing German experience in the Ukrainian early childhood education system have been identified, taking into account national characteristics and contemporary challenges.